Liver Immune Profiling Reveals Pathogenesis and Therapeutics for Biliary Atresia - Wang, Jun; Xu, Yanhui; Chen, Zhanghua; Liang, Jiankun; Lin, Zefeng; Liang, Huiying; Xu, Yiping; Wu, Qi; Guo, Xuanjie; Nie, Junli; Lu, Bingtai; Huang, Bing; et al. (Cell, 2020)
Biliary atresia (BA) is a severe cholangiopathy that leads to liver failure in infants, but its pathogenesis remains to be fully characterized. By single-cell RNA profiling, we observed macrophage hypo-inflammation, Kupffer cell scavenger function defects, cytotoxic T cell expansion, and deficiency of CX3CR1 effector T and natural killer (NK) cells in infants with BA. More importantly, we discovered that hepatic B cell lymphopoiesis did not cease after birth and that tolerance defects contributed to immunoglobulin G (IgG)-autoantibody accumulation in BA. In a rhesus-rotavirus induced BA model, depleting B cells or blocking antigen presentation ameliorated liver damage. In a pilot clinical study, we demonstrated that rituximab was effective in depleting hepatic B cells and restoring the functions of macrophages, Kupffer cells, and T cells to levels comparable to those of control subjects. In summary, our comprehensive immune profiling in infants with BA had educed that B-cell-modifying therapies may alleviate liver pathology.